High school teachers’ perception of AR and VR in English language teaching and learning activities : A developing country perspective - Annamalai, Nagaletchimee; Uthayakumaran, Arulselvi; Zyoud, Samer H. (Springer, 2023)
AR and VR are new introductions in many developing countries, including Malaysia. The present study conducted a qualitative case study with 23 high school teachers and investigated their perceptions of AR and VR in English language teaching and learning activities. A semi-structured interview was employed to collect the data. The data was analysed based on the thematic analysis suggested by Braun and Clarke (Qualitative Research in Psychology, 3(2), 77–101, 2006). The findings revealed positive and negative perceptions of integrating AR and VR in English language teaching and learning activities. The positive themes were related to effective English language learning, engaging students, bringing your own device (BYOD) and active learning. The negative perceptions were related to time-consuming and health-related matters. The study further suggested approaches that might be effective in adopting AR and VR in English language teaching and learning activities. It is hoped that the outcome of the present study can provide insights for teachers, curriculum planners, and policymakers to consider the strengths and limitations of AR and VR before it is integrated into English language teaching and learning activities.